Sick Justice : Inside the American Gulag - Goldman, Ivan G. (Book collections on Project MUSE., 2013)
"In America, 2.3 million peopleùa population about the size of HoustonAEs, the countryAEs fourth-largest cityùlive behind bars. Sick Justice explores the economic, social, and political forces that hijacked the criminal justice system to create this bizarre situation. Presenting frightening true stories of (sometimes wrongfully) incarcerated individuals, Ivan G. Goldman exposes the inept bureaucracies of AmericaAEs prisons and shows the real reasons that disproportionate numbers of minorities, the poor, and the mentally ill end up there. Goldman dissects the widespread phenomenon of jailing for profit, the outsized power of prison guardsAE unions, CaliforniaAEs exceptionally rigid three-strikes law, the ineffective and never-ending war on drugs, the closing of mental health institutions across the country, and other blunders and avaricious practices that have brought us to this point. Sick Justice tells a big, gripping story thatAEs long overdue. By illuminating the systemAEs brutality and greed and the prisonersAE gratuitous suffering, the book aims to be a catalyst for reform, complementing the work of the Innocence Project and mirroring the effects of Michael HarringtonAEs The Other America: Poverty in the United States (1962), which became the driving force behind the war on poverty"--Publisher's description.